REFRAMING STRATEGIC HUMAN RESOURCE MANAGEMENT: HUMAN CAPITAL AS A KEY MECHANISM OF ORGANIZATIONAL DYNAMIC CAPABILITIES - Hema Herman; Tetra Hidayati (RADJA PUBLIKA, 2026)
Changes in the global organizational environment, characterized by technological turbulence, market uncertainty, sustainability pressures, and institutional complexity, have raised fundamental theoretical issues in the strategic management literature, particularly regarding how organizations build sustainable and adaptive capacity. Recent literature suggests that organizational failure is more often rooted in weak internal capabilities to execute and update strategy than in strategy formulation errors, making Strategic Human Resource Management a central issue in contemporary discourse. However, a review of the past five years has revealed the main limitations of the SHRM literature, which is still dominated by tests of direct relationships with performance or competitive advantage, with inconsistent empirical results and a lack of mechanistic explanations integrated with the resource-based view and dynamic capability. The literature also shows the fragmented use of mediating variables such as human capital without a coherent, process-based causal framework. This literature review aims to develop a conceptual synthesis that integrates SHRM, human capital, and dynamic capabilities into a consistent, mechanism-based explanatory framework. The approach used is an integrative literature review with a systematic search of reputable international databases for the period 2020–2025, accompanied by citation-chaining and thematic and configurative synthesis. The main conceptual findings confirm that SHRM functions as a process-based strategic architecture that shapes the quality of human capital as a microfoundation for the formation of dynamic organizational capabilities. The theoretical contribution of this study lies in clarifying the causal mechanisms of SHRM through human capital and expanding the theory's boundaries to digital and algorithmic contexts. Further research should examine time-based designs, cross-level mechanisms, and technological boundary conditions in the development of contemporary SHRM theory.